Thermoluminescence characteristic of CaSO4:Dy on β and γ radiation. (June 2019) - Nuraeni, N; Kartikasari, D; Yani, S; Hiswara, E; Haryanto, F; Iskandar, F; Waris, A
Abstract: The research on the developments of thermoluminescence (TL) material in nano- and microstructure are increasing in recent years. There are many new techniques developed for preparing TL material that aim to improve and investigate the structure, morphology, and TL characteristics. In this study, the TL characteristics of CaSO4 doped with Dysprosium (Dy) were being observed. CaSO4 :Dy was performed by co-precipitation method with 0.1 mol% Dy concentration. The obtained sample was irradiated with Cs-137 for gamma source and Sr-90 for beta source with doses of 5, 10, 15, 20 and 25 mGy. After irradiation, the structure, morphology, and TL response were observed by using XRD, SEM, and TLD Reader Harshaw 3500. XRD results showed that the average crystallite size for CaSO4 :Dy were 58 nm. But, the presence of dysprosium could not be clearly observed from XRD results. The characterization results from SEM for CaSO4 :Dy had shape resembling needle-like crystal. The TL response of CaSO4 :Dy was compared from beta and gamma radiation source. TL responses for Cs-137 source were 26.56, 34.09, 51.85, 75.97, and 86.29 nC for 5, 10, 15, 20, and 25 mGy, respectively. Sr-90 source with the same dose obtained TL responses as follows: 35.67, 68.60, 100.87, 121.69, and 179.85 nC. The shapes of the glow curves were almost identical, but these curves had different intensities. The TL response from β-ray source obtained a higher intensity than from γ-ray source because the beta source is a particle with mass so that it will have more interaction than gamma source in TLD material.